Digital activation theory. Theoretical-methodological proposal of the communicative practices of networked social movements - Bustamante Farías, Óscar (2019)
The article formalizes a theoretical-methodological proposal of the communicative practices of networked social movements as a new cycle of collective action. Digital activation is proposed as an emergent and inter- disciplinary object of study, which consists of contexts and dimensions that can be studied under the light of “deep hermeneutics”, and that represents a contribution to the sub-field of political communication.